Altered association between cortisol and adrenocorticotropic hormone levels in the early stage of type 2 diabetic ketoacidosis - Wang, Liang; Meng, Xiaomei; Tang, Yuxiao; Hao, Yaping (Frontiers in Endocrinology, 2025)
ObjectivesIn the early stages of various critical infections and diseases, altered association of cortisol and adrenocorticotropic hormone (ACTH) levels occurs, with cortisol levels increasing and ACTH levels remaining normal or decreasing. This study aimed to explore the relationship between ACTH and cortisol levels in patients with diabetic ketoacidosis (DKA) and the influence of the severity of DKA.MethodsA total of 106 type 2 diabetes patients with DKA admitted to the Endocrinology Department of Yantai Yuhuangding Hospital from February 2018 to May 2023 were divided into groups without (n=54) and with bacterial infection (n=52). Twenty type 2 diabetes patients without infection or DKA admitted during the same period were included as the control group. Cortisol and ACTH levels were measured on the first day of admission and the day after DKA correction for patients with DKA and on the first day of admission and the day before discharge for the control group.ResultsCompared with the control group, the DKA groups both with and without infection had significantly higher cortisol levels (P<0.05) and significantly lower ACTH levels (P<0.01) at admission. DKA patients with infection had significantly higher cortisol levels at admission than those without infection (734.51 ± 348.69 nmol/L vs 508.79 ± 268.72 nmol/L, P<0.01), while ACTH levels did not differ significantly between the two groups (P>0.05). After correction of DKA, no differences in cortisol or ACTH levels were observed among the three groups. Compared with levels at admission, DKA patients both with and without infection had lower cortisol levels and higher ACTH levels after DKA correction (all P<0.001). Multiple stepwise regression analysis showed that for all DKA patients and for subgroups with and without infection, the cortisol level at admission was independently positively correlated with the ACTH level and negatively correlated with the bicarbonate level (both P<0.01).ConclusionsIn the early stage of DKA, a phenomenon of altered association between cortisol–ACTH occurs and is especially prominent in DKA patients with infection. This altered association between cortisol–ACTH disappears after DKA correction, and the severity of DKA is an independent influencing factor on the cortisol level in early-stage DKA.